2020
DOI: 10.1055/s-0040-1716877
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Sparing Surgery in Mature Ovarian Teratomas in Children: A 20-Year Single-Center Experience

Abstract: Introduction Despite its benign nature, possible bilateral presentation, and a very good prognosis, ovarian sparing tumorectomy (OST) in mature ovarian teratoma (MOT) is not commonly performed. Unilateral oophorectomy has physiological consequences, while bilateral is devastating. The aim of this study is promotion of OST in MOT among children. Materials and Methods We reviewed 120 patients operated for MOT between August 1999 and 2019. Results Ovariectomy was performed in 15 patients (14 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
2
14
0
2
Order By: Relevance
“…In accordance with other studies, our experience showed that laparoscopy and laparotomy can both be safely practiced for OMT surgery without any influence on its recurrence 19,25 . Laparoscopy has the advantages of decreasing postoperative pain, complications, and length of hospitalization 6–8,21,26–28 . It also minimizes postoperative adhesions, which may have an impact on fertility 6,7,25,28 .…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In accordance with other studies, our experience showed that laparoscopy and laparotomy can both be safely practiced for OMT surgery without any influence on its recurrence 19,25 . Laparoscopy has the advantages of decreasing postoperative pain, complications, and length of hospitalization 6–8,21,26–28 . It also minimizes postoperative adhesions, which may have an impact on fertility 6,7,25,28 .…”
Section: Discussionsupporting
confidence: 85%
“…Bilateral forms and OMT second events were reported in 5% and 8.3% of cases in our cohort, which may lead to additional amputation of the ovarian tissue. All these features plead to conservative surgery to preserve the ovarian tissue as much as possible 8,11,14,27,28,33 . In our series, all patients maintained at least one ovary even after recurrence.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations